IMPLICATIONS OF WATER CHANNEL PROTEINS (AQUAPORINS AND RELATIVES) IN EPILEPSIES - BENGA, Ileana (Studia Universitatis Babeș-Bolyai Chemia, 2021)
The abundant evidence linking epilepsy with hydroelectrolytical changes in epilepsy reported in the medical literature for over 9 decades is reviewed. Our work on this topic is presented, including the detection by NMR of a decreased water permeability of the red blood cells (RBCs) from children with epilepsy compared with control children. This was interpreted as a generalized membrane defect in epilepsy. The subsequent program of research performed by Gh. Benga’s group in Cluj-Napoca led to the discovery of the first water channel protein (WCP) in the RBC membrane, protein later called aquaporin1 (AQP1). A lot of WCPs (AQPs and relatives) have been identified later by various authors, in the body of humans and many other species. The physiological roles of WCPs from the central nervous system (CNS) and their implications in epilepsy and other neurological diseases are reviewed, including the information published in the last months.